2016
DOI: 10.1097/jcp.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Movement Disorders in Adults With Intellectual Disability and Behavioral Problems Associated With Use of Antipsychotics

Abstract: The prevalence of movement disorders in people with ID and behavioral problems is high, especially in ID patients using antipsychotics. More attention is needed for these movement disorders and their potential impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…In once recent study of hospitalised patients with borderline-mild ID and challenging behaviour, almost half were found to have a movement disorder, and the presence of movement disorder was more likely in those prescribed antipsychotic medication. 21 The most common type was parkinsonism, as in our study. De Kuijper and colleagues in the Netherlands report that just over half of their sample with ID who had been taking antipsychotic drugs for more than a year had evidence of movement side effects.…”
Section: Discussionsupporting
confidence: 75%
“…In once recent study of hospitalised patients with borderline-mild ID and challenging behaviour, almost half were found to have a movement disorder, and the presence of movement disorder was more likely in those prescribed antipsychotic medication. 21 The most common type was parkinsonism, as in our study. De Kuijper and colleagues in the Netherlands report that just over half of their sample with ID who had been taking antipsychotic drugs for more than a year had evidence of movement side effects.…”
Section: Discussionsupporting
confidence: 75%
“…Not surprisingly, hospitalised ADEs in PwNDD were primarily caused by psychotropic medications. This is consistent with findings in previous studies (Ji & Findling 2016;Paton et al 2016;Scheifes et al 2016a). It is also alarming that opioid-related ADEs were prevalent in PwNDD as well as the general population.…”
Section: Discussionsupporting
confidence: 92%
“…; Scheifes et al . ). It is also alarming that opioid‐related ADEs were prevalent in PwNDD as well as the general population.…”
Section: Discussionmentioning
confidence: 97%
“…The risks of prescribing antipsychotic drugs to patients with dementia have been well documented [14]. Antipsychotic drugs may cause extrapyramidal side effects [5] and studies have shown that the newer second-generation atypical antipsychotic drugs are also associated with an increased risk of stroke [1, 69]. Regulatory bodies in several countries have issued warnings, guidance and advice aiming to reduce inappropriate prescribing of antipsychotic drugs to patients diagnosed with dementia [10–21].…”
Section: Introductionmentioning
confidence: 99%